An assessment of the Land Transportation franchising and regulatory Board's (LTFRB) efficiency and effectiveness in the enforcement of the prescribed fare matrix - Ferando, Arlene Barredo
The study aimed at assessing the efficiency and effectiveness of the Land Transportation Franchising and Regulatory Board in the implementation of the order with regards to the prescribed fare matrix.